Fast into the night : a woman, her dogs, and their journey north on the Iditarod Trail - Moderow, Debbie Clarke (Houghton Mifflin Harcourt, 2016)
Describes the author's experiences as a middle-aged mom whose initial resolve to train for and complete the Iditarod failed when her dogs refused to finish the race, detailing how she overcame daunting challenges to succeed during a second attempt. --Publisher's description.